Reproductive and behavioral aspects of red-winged tinamous (Rhynchotus rufescens) in groups with different sex ratios - Cromberg, VU [UNESP]; Stein, MS [UNESP]; Boleli, IC [UNESP]; Tonhati, Humberto [UNESP]; Queiroz, SA [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2007)
The aim of this research study was to evaluate the reproductive performance of tinamous submitted to five different male:female ratios. The study was carried out with 72 birds in a randomized experimental design with 4 replications. Tinamous were housed in cages, using the ratios of one (1:1), two (2:1), three (3:1) and four (4:1) females per male, and also one male was housed with three females individually (3R:1), in a rotational system. Reproductive records of the breeding season from September 2004 to March 2005 were used. The reproductive traits studied were: number of eggs laid, fertility, and percentage of eggs damaged and cracked by pecking. Nonparametric analyses of these traits were performed using Kruskal-Wallis test. Two replications of treatments 1:1 and 4:1, and one of treatment 2:1 were video-taped for three days, 12 hours/day. The videotapes were sampled according to the scan method to fit an ethogram. Birds were also watched for one hour per day to study dominance and agonistic behavior. None of the reproductive traits was affected by mating sex ratio (p<0.05). Female dominance could be related to displacement behavior (r=1.00), and male sitting in immobility plus sitting in activity behaviors were related to lower number of damaged eggs (r=-0.90). Social dominance was indirectly determined by displacement behavior in the study situation. A large number of damaged eggs occurred in all treatments, thereby not allowing a clear conclusion on the best male:female ratio.
Keywords: Agonistic behavior; Domestication; dominance; laying birds; Tinamous